THE SINGULARIZATION OF HISTORY: SOCIAL HISTORY AND MICROHISTORY WITHIN THE POSTMODERN STATE OF KNOWLEDGE. - Magnusson, Sigurdur Gylfi (Journal of Social History)
Focuses on the rise in microhistory across the globe in the past decade and on the topics of microhistorical research. Emphasis on the theoretical orientations of all microhistorians; Proposal of the approach, 'singularization of history'; Criticisms on the conventional theoretical framework of microhistorical research.